Bank performance and board of directors attributes by Islamic banks. Issue 3 (17th August 2015) - Bukair, Abdullah Awadh; Abdul Rahman, Azhar
Abstract : Purpose: – The purpose of this paper is to examine the relationship between board structure (consisting of board size, board composition, CEO role duality and chairman composition), investment account holders (IAHs) and social contribution and the bank performance in one of the fastest-growing industries, Islamic banking. Design/methodology/approach: – A generalized least square (GLS) regression model was used to investigate such relationship applying data from a sample of 40 Islamic banks operating in Gulf Cooperation Council (GCC) countries over the period of 2008 until 2011. Findings: – The results show that both size and composition of the board have a negative effect on bank performance. On the other hand, the separation of CEO and chairman roles and the IAHs have no effect, while the chairman independence has a positive impact. As for the control variables, bank size positively influences bank performance whereas leverage has a negative effect. Zakah and gross domestic product produce no significant effect on bank performance. Research limitations/implications: – Even though the model has explained the significant part of the variation in performance, there are other factors considered as noise in the model which are unexplained due to the lack of data. As such, other mechanisms of corporate governance (CG) comprising attributes of the remuneration and nominating committees and ownership structure may be used in future research. The sample size is also limited; thus, in future research, the sample size could be increased by including Islamic banks operating in all Middle East countries. Practical implications: – The results suggest that to yield a better bank performance, Islamic banks should enhance the effectiveness of CG through the board of directors (BODs), whereby any decisions made by the BODs would lead to greater investors' confidence in the market. The results suggest that policymakers should impose new mechanisms that could impact the effectiveness and compliance of BODs on the code of CG and guidelines of micro-finance, in general, and among Islamic banks, in particular. The community also has the right to know up to what extent are the Islamic banks are in compliance with Shariah principles and rules and the impact of their transactions on the society's welfare. Originality/value: – BODs' failures are the primary reason for the recent financial collapses, and Islamic banks are not spared from these events. Even though many studies have examined the influence of BODs effectiveness on the performance of conventional banking industry over time, studies on the Islamic financial institutions are quite scarce. In addition, the results obtained by the studies on conventional banks may not be applicable to Islamic banks. This is because the BODs of Islamic banks discharge their responsibilities and duties along with the existence of the Shariah supervisory board (a multi-layer structure), which is quite different from the CG structure in conventional banks that is dependent on the BODs (a single-layer). Therefore, this research attempts to fill the gap in the literature by addressing this issue in the Islamic banking industry by using a stakeholder theory based on Islamic perspective which has not been used yet in previous studies.